Case Study of Customer Satisfaction In A State-Owned Construction Companies - Pradhito Januadhistianto; Jati Utomo Dwi Hatmoko; Sriyana Sriyana (Eduvest - Journal of Universal Studies, 2024)
Customer satisfaction has been recognised by researchers as one of the main factors for the success of project. Customer satisfaction to build a loyal relationship between users and service providers is an interesting challenge. This study aims to provide information from literature regarding the on factors that affect customer satisfaction, and to determine the assessment of customer satisfaction with the performance of PT PP Persero Tbk, especially in the building division. The study from 28 literatures show that the quality of work and a professional team are the factors that most affect customer satisfaction. The results of the customer satisfaction assessment (CSS) of PT PP Persero Tbk state that the quality of human resources and interpersonal communication with customers is the most valued by customers in assessing project performance. These result prove that a professional team consisting of quality human resources is important in providing customer satisfaction. This research only focuses on subjective assessment methods applied to construction management to obtain customer satisfaction.